Evaluating the efficacy of an information-based residential outdoor water conservation program. (10th September 2018) - Landon, Adam C.; Woodward, Richard T.; Kyle, Gerard T.; Kaiser, Ronald A.
Abstract: Information-based policy instruments are some of the most commonly used tools for influencing consumers' water use in the residential sector. However, their ability to change behavior remains an area in need of further research. This study describes the evaluation of an information-based demand management program, rooted in normative comparison, designed to increase the efficiency of households' residential outdoor water use. Results indicate that the program had an impact on water use among households that received persuasive messages regarding their past consumption, compared to estimates of lawn water requirements and the water use of neighbors. Additionally, the results demonstrate that the treatment effect gets stronger over time and varies among message recipients as a function of baseline water use. Unanticipated effects of the administration of the messages show an increase in water use among the lowest consuming households. Top users reduced their water use significantly as a function of the persuasive message. The findings suggest that utilities seeking to augment users' water consumption through persuasion must be cognizant of the way that messages are framed, and who receives them, or potentially face unanticipated side effects, and that message repetition may have some additionality. Highlights: Quasi-experiment used to evaluate voluntary water conservation program. Normative feedback messages reduced high water using households' consumption. Treatment effects get stronger with repetition of message/time. Low water using households increase use as a function of message receipt.